15 minute vegan : fast, modern vegan cooking - Beskow, Katy (Quadrille, 2017)
15 Minute Vegan features a hundred brand new vegan recipes that can be prepared in mere moments. Using ingredients that are available in supermarkets, the recipes are as easy as can be - from shopping to cooking to serving. The book starts with Katy's introduction to vegan cooking and cooking, with advice on the equipment you need to make your cooking go faster, plus essential storecupboard ingredients. In chapters covering Breakfast, Light Bites, Mains, Essentials and Sweet Stuff, Katy offers straightforward recipes and tips about preparation, freezing and storing. Whether you're already eating vegan or just want to try something new, nothing could be simpler and faster.